Approaches to Evaluation: in Pursuit of Appropriacy For EFL Pre-Service Teacher Training Programs in Indonesia - Didin Nuruddin Hidayat (Universitas Muhammadiyah Mataram, 2018)
Evaluation has the potential to support the improvement of education as well as its specific programs, products, and materials. Also, evaluation can uncover the relevance, effectiveness, and efficiency of an education program. Another potential role of evaluation is that it can identify areas for improvement, which further can help develop a more efficient program in the future. The present study seeks to investigate the most appropriate approach to evaluation for the EFL pre-service teacher training programs in Indonesia. Numerous potential approaches were identified and discussed: Pseudoevaluations, Questions Methods-Oriented, Improvement Accountability, and Social Agenda/Advocacy. The present study argues that the Improvement/Accountability Approaches are the most suitable evaluation approach to apply to the pre-service EFL teacher training programs in Indonesia, due to its strength in the philosophical stance that fits with the Indonesian context. Also, the purpose of the evaluation and the various types of informants offer by the approach add to the appropriacy. The study may provide significant contributions to better design more effective teacher training programs, which will lead to producing more qualified graduates